2021
DOI: 10.3390/curroncol28020127
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy in Breast Cancer: Review of the Evidence and Conditions That Facilitated Its Use during the Global Pandemic

Abstract: Practice and behaviour change in healthcare is complex, and requires a set of critical steps that would be needed to implement and sustain the change. Neoadjuvant chemotherapy for breast cancer is traditionally used for locally advanced disease and is primarily advantageous for surgical downstaging purposes. However, it does also offer patients with certain biologic subtypes such as the triple negative or Her2 positive breast cancers the opportunity to improve survival, even in early stage disease. During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Chemotherapy is one of the main treatments of cancer and is usually performed as neoadjuvant and adjuvant therapy (12,13). Although chemotherapy can improve the overall survival and prognosis of cancer patients, chemoresistance remains a clinical obstacle that needs to be overcome due to the diversity, heterogeneity, and adaptability to environmental alters in clinics (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is one of the main treatments of cancer and is usually performed as neoadjuvant and adjuvant therapy (12,13). Although chemotherapy can improve the overall survival and prognosis of cancer patients, chemoresistance remains a clinical obstacle that needs to be overcome due to the diversity, heterogeneity, and adaptability to environmental alters in clinics (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The use of NAC was 13.5% in the Commercial cohort and 6.7% in the Medicare cohort reflecting an increasing trend in NAC utilization, consistent with prior studies. 44 46 We found that NAC was associated with a 29% decreased risk of reoperations in the Commercial cohort and a 35% decreased risk in the Medicare cohort. Lower rates of reoperation are expected in this subset of patients as tumor response to neoadjuvant therapy allows for patients to become better candidates for BCS with a higher chance of achieving negative margins.…”
Section: Discussionmentioning
confidence: 75%
“…Still, this is somewhat counterintuitive, as cytotoxic chemotherapy and radiation are known to be myelosuppressive and surgery as well may predispose to infectious risk 43 . At the same time, we also speculate that many clinicians, when understanding the risk of SARS-CoV-2 infection, were already more careful in only selecting robust patients for cancer therapy and excluding higher risk patients 44 . Given the role of estrogen in enhancing adaptive and humoral immunity, we had hypothesized that patients receiving endocrine therapy would have worse outcomes from COVID-19 24, 25 .…”
Section: Discussionmentioning
confidence: 91%